The Threshold Effects on Consumer Choice and Pricing Decisions - Wang, Ruxian (Manufacturing and Service Operations Management, 2022)
Problem definition: This paper investigates the threshold effects on the consideration set formation for consumers and the associated pricing decisions for firms. Academic/practical relevance: In the class of random utility maximization choice models, consumers choose the alternative with the largest utility after resolving utility uncertainties for all options. However, in practice, consumers may not inspect all available alternatives due to bounded rationality or search cost. Methodology: This paper incorporates bounded rationality into consumer choice behavior: in the first stage, a representative consumer forms her consideration set by removing alternatives whose nominal utility is lower than the largest by a threshold; in the second stage, she examines all alternatives in her consideration set and chooses the one with the highest realized utility. Results: For the Gumbel-distributed random utilities, we derive the two-stage threshold multinomial logit model with a consideration set. For the pricing problem, we show the quasi-same-markup/same-utility policy is optimal: high-cost products charge the prices such that their profit markups are the same, and low-cost products charge prices such that their nominal utilities are the same. For the price competition, there may exist zero, one, two, or infinite Nash equilibria, depending on the magnitude of the threshold effects. Managerial implications: Our analysis shows that the consideration set and bounded rationality play an important role in consumer choice behavior, so they should be taken into account in firms’ decision making.